Flowery Inductive Rhetoric Meets Creative Deductive Arguments Becoming Transnational Researcher-writers - Singh, Michael; Fu, Dongquing (Penerbit Universiti Sains Malaysia (USM Press), 2008)
Sometimes students from China are characterised as writing inductively, using flowery prose. The proposition explored in this paper is that having higher degree research (HDR) students from China develop their critiques of stereotypes of "Asian students" provides useful insights into where existing supervisory pedagogies might be reworked to enhance their capabilities for writing scholarly arguments. Using evidence from a textbook used by students studying English as a foreign language in China this paper documents the different models of deductive argumentation they are taught. Certain writing conventions for constructing arguments—theses—are required in learning to produce research and to become a transnational researcher-writer. This paper opens up to exploration of the question of what can western supervisors and their Chinese students do.